(untitled) (Itinera, 2013)
The paper discusses Woody Allen’s 1982 movie A Midsummer’s Night Sex Comedy and focuses on the dialectic between the characters of Andrew (Woody Allen) and Leopold (José Ferrer) and, in particular, on their different attitudes towards the notion of supernatural. I argue that in order to make sense of this dialectic we must embrace a somewhat Wittgensteinian view of what it is to say that something is supernatural.